Dynamic response of an embedded flexible foundation of general shape in a transversely isotropic and multilayered half-space. Issue 139 (December 2020) - Han, Zejun; Pan, Ernian; Zhang, Zhiqing
Abstract: A new semi-analytical method is developed for solving the dynamic response of an embedded flexible foundation of general shape in a transversely isotropic and multilayered half-space. It is based on the hybrid Green's functions (GFs) and finite-element method (FEM) via the modified subtraction method. The GFs in the multilayered half-space are derived by virtue of the dual variable and position (DVP) method whilst the FEM is utilized to discretize the domain of the embedded foundation. Making use of the modified subtraction method, the GFs and FEM formulations are combined to derive the dynamic impedance matrix of the embedded foundation. After verifying the accuracy and stability of the proposed algorithm, numerical studies are carried out to investigate the effect of the foundation modulus, half-space anisotropy, and layering on the dynamic impedance matrix of the embedded foundation. Results show that these factors could significantly affect the dynamic impedance matrix of the foundation, which could provide reference for practical engineering design. Highlights: Green's functions and DVP for layered structures. Combination of FEM and Green's functions via modified subtraction method. General dynamic soil-structure interactions. Embedded flexible foundation of arbitrary shape. Transverse isotropic property of the multi-layered soil is feasible.